Analisis Faktor-Faktor Yang Mempengaruhi Loyalitas Pelanggan Serta Dampaknya Terhadap Keunggulan Bersaing - Tahuman, Zainuddin (Universitas Sam Ratulangi, 2016)
Competitive environment is getting tougher and the reduction of sales growth need to look that national private company can growing and increasing the marketing performance. Inthis case company must have high competitive advantages that survice and well operation. The result of hypothesis test find that brand reputation has effect on customer satisfaction. Brand reputation has effect significantly on customer loyalty. Service quality has significantly effect on customer satisfaction. Service quality has no significantly effect on customer loyalty.Customer satisfaction has significantly effect on customer loyalty. Customer loyalty has significantly effect on company competitive advantageKeywords: Loyalty, Competitive Advantage, Service Quality, Brand Reputation, Satisfaction